2021
DOI: 10.3390/math10010082
|View full text |Cite
|
Sign up to set email alerts
|

f(R,T)-Gravity Model with Perfect Fluid Admitting Einstein Solitons

Abstract: f(R,T)-gravity is a generalization of Einstein’s field equations (EFEs) and f(R)-gravity. In this research article, we demonstrate the virtues of the f(R,T)-gravity model with Einstein solitons (ES) and gradient Einstein solitons (GES). We acquire the equation of state of f(R,T)-gravity, provided the matter of f(R,T)-gravity is perfect fluid. In this series, we give a clue to determine pressure and density in radiation and phantom barrier era, respectively. It is proved that if a f(R,T)-gravity filled with per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In this context, one notes that η$$ \eta $$‐Einstein solitons can be viewed as a generalization of η$$ \eta $$‐Ricci solitons. In the recent years, Einstein and η$$ \eta $$‐Einstein solitons have been considered by several mathematicians such as [8, 13–19] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, one notes that η$$ \eta $$‐Einstein solitons can be viewed as a generalization of η$$ \eta $$‐Ricci solitons. In the recent years, Einstein and η$$ \eta $$‐Einstein solitons have been considered by several mathematicians such as [8, 13–19] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that their model represent the dark matter era for the obtained RSVFs. Siddique et al [24] worked in f (R, T)-gravity and showed that if a perfect fluid spacetime in f (R, T)-gravity admits an Einstein soliton and the corresponding RSVF is a Killing vector field, then the scalar curvature will be constant. Siddique [25] worked on perfect fluid spacetime in f (R, T) gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Siddique et al [24] worked in f (R, T)-gravity and showed that if a perfect fluid spacetime in f (R, T)-gravity admits an Einstein soliton and the corresponding RSVF is a Killing vector field, then the scalar curvature will be constant. Siddique [25] worked on perfect fluid spacetime in f (R, T) gravity. The author obtained modified Poisson and Liouville equations from the Ricci soliton equation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here α, β are scalars and u k is a 1-form [12][13][14][15][16][17][18]. A perfect fluid spacetime is pictured as a Lorentzian quasi-Einstein manifold given that u k is a unit time-like vector field [14,19,20]. These manifolds emerged during the investigation of Einstein's field equation.…”
Section: Introductionmentioning
confidence: 99%